2017
DOI: 10.1038/s41523-016-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification, validation, and targeting of the mutant p53-PARP-MCM chromatin axis in triple negative breast cancer

Abstract: Over 80% of triple negative breast cancers express mutant p53. Mutant p53 often gains oncogenic function suggesting that triple negative breast cancers may be driven by p53 protein type. To determine the chromatin targets of this gain-of-function mutant p53 we used inducible knockdown of endogenous gain-of-function mtp53 in MDA-MB-468 cells in conjunction with stable isotope labeling with amino acids in cell culture and subcellular fractionation. We sequenced over 70,000 total peptides for each corresponding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 53 publications
9
85
1
Order By: Relevance
“…MCMs are also involved in apoptosis pathways and inhibit some apoptotic proteins. In triple-negative breast cancer, MCM2-7 complex was reported to participate in a high mutant p53-chromatin-associated pathway [95]. In this research, a protein-protein interaction between overexpressed mutant p53 and MCM2/4 was directly detected.…”
Section: Effects Of Mcms In Cellular Signalingmentioning
confidence: 70%
See 1 more Smart Citation
“…MCMs are also involved in apoptosis pathways and inhibit some apoptotic proteins. In triple-negative breast cancer, MCM2-7 complex was reported to participate in a high mutant p53-chromatin-associated pathway [95]. In this research, a protein-protein interaction between overexpressed mutant p53 and MCM2/4 was directly detected.…”
Section: Effects Of Mcms In Cellular Signalingmentioning
confidence: 70%
“…Based on public databases, strong positive coexpression was observed among MCM2-7 genes [94]. In triple-negative breast cancer, protein-protein interaction between Mcm2 and Mcm4 was verified with proximity ligation assay [95].…”
Section: Cross-talk In MCM Familymentioning
confidence: 98%
“…Specifically, CXCL12 seems to play a detrimental role in breast cancer; its expression in patients has been extensively studied. High CXCL12 levels are present in patients with lymph node and brain metastasis and inversely correlate with the overall survival [ 32 , 33 , 34 ]. CXCL12 in breast cancer is typically released from stromal cells, and in TNBC it is secreted by a specific immunosuppressive subset of fibroblasts [ 33 , 35 ].…”
Section: The Cxcr4 Chemokine Receptor Controls Multiple Aspects Ofmentioning
confidence: 99%
“…They are stronger inducers of cancer cell migration. High levels of CXCL12 and CXCL16 in CAFs from human brain cancer metastasis attract breast cancer cells via the CXCR4-CXCL12 and CXCR6-CXCL16 pathways [ 33 ].…”
Section: The Cxcl12/cxcr4 Signaling Promotes Fibroblasts Transformmentioning
confidence: 99%
“…It was functionally demonstrated that miR-498 inhibits BRCA1 in breast cancer cell lines, and showed that inhibition of miR-498 led to reduced proliferation in the triple negative cell line Hs578T and results indicate that miR-498 regulates BRCA1 expression in breast cancer and its overexpression could contribute to the pathogenesis of sporadic TNBC via BRCA1 downregulation. 21 an oncomiR was proven to regulate PTEN by targeting the mRNA 3′UTR, leading to an anti-apoptosis effect in TNBC (32). Specifically, miR-21 exhibits a higher expression level in TNBC than non-TNBC, and it is positively correlated with a poor clinical outcome.…”
Section: Poly(adp-ribose) Polymerase (Parp):-mentioning
confidence: 99%